Intrathecal morphine administration reduces postoperative pain and peripheral endocannabinoid levels in total knee arthroplasty patients: a randomized clinical trial - Martin Kaczocha; Syed Azim; James Nicholson; Mario J. Rebecchi; Yong Lu; Tian Feng; Jamie L. Romeiser; Ruth Reinsel; Sabeen Rizwan; Shivam Shodhan; Nora D. Volkow; Helene Benveniste (BMC Anesthesiology, 2018)
Abstract Background The primary goal of this study was to determine whether administration of intrathecal morphine reduces postoperative pain. The secondary goal was to determine the effect of intrathecal morphine upon circulating levels of the weakly analgesic endocannabinoids, anandamide (AEA) and 2-arachidonoylglycerol (2-AG), and the related lipids palmitoylethanolamide (PEA) and oleoylethanolamide (OEA). Methods Forty two total knee arthroplasty (TKA) patients were enrolled in a prospective, double-blinded, randomized study. The intervention consisted of intrathecal morphine (200 μg) or placebo administered at the time of the spinal anesthesia. Postoperative pain was measured during the first 4 h after surgery while serum levels of AEA, 2-AG, PEA, OEA, and cortisol were measured at baseline and 4 h after surgery. Results Administration of intrathecal morphine reduced postoperative pain 4 h after TKA surgery compared to placebo (p = 0.005) and reduced postoperative systemic opioid consumption (p = 0.001). At baseline, intrathecal morphine led to a significant reduction in AEA, 2-AG, and OEA levels but did not affect PEA or cortisol levels. In patients administered intrathecal placebo, 2-AG levels were elevated 4 h after surgery; whereas patients receiving intrathecal morphine showed reductions in AEA, PEA, and OEA when compared to placebo. At 4 h after TKA surgery cortisol levels were significantly elevated in the placebo group and reduced in those receiving morphine. Conclusions These results indicate that intrathecal morphine reduces postoperative pain in TKA patients. Furthermore, activation of central opioid receptors negatively modulates the endocannabinoid tone, suggesting that potent analgesics may reduce the stimulus for production of peripheral endocannabinoids. This study is the first to document the existence of rapid communication between the central opioid and peripheral endocannabinoid systems in humans. Trial registration This trial was registered retrospectively. Trial registry: NCT02620631. Study to Examine Pain Relief With Supplemental Intrathecal Morphine in TKA Patients, NCT02620631, 12/03/2015.